DEVELOPMENT OF PREZI-BASED LEARNING MEDIA TO IMPROVE STUDENTS' LEARNING OUTCOMES IN THE FIQIH SUBJECT AT MAN 1 SUNGAI PENUH: PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS PREZI UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA MATA PELAJARAN FIQIH DI MAN 1 SUNGAI PENUH - Muhammad Syahril; Gusril Kendi; Khadijah Khadijah (STKIP Pesisir Selatan, 2026)
This study aims to develop Prezi-based learning media for Fiqh subjects on buying and selling transactions for Madrasah Aliyah (MA) students. This development was carried out to address students' low understanding due to the delivery of material that tends to be abstract and conventional. This study uses a Research and Development (R&D) approach with the ADDIE (Analyze, Design, Develop, Implement, Evaluate) development model. The research instruments include expert validation questionnaires (material, media, language), practicality questionnaires, and learning outcome tests (pretest and posttest). Data were analyzed descriptively quantitatively and qualitatively, and strengthened by paired sample t-tests to see the effectiveness of the media. Prezi-based media was declared very valid with scores from material experts (85%), media experts (91.5%), and language experts (96%). The practicality level reached 93% (very practical). This media was proven to be effective in improving student learning outcomes from an average pretest of 64.29 to 86.57 in the posttest with a Sig. (2-tailed) value <0.05. The novelty of this research lies in the integration of the Prezi platform, which offers an infinite canvas and a zoomable user interface (ZUI) feature to dynamically visualize the structure of Fiqh Muamalah concepts. Unlike static media, this development suggests integrating contemporary transactions (COD and e-wallet) to adapt the classic material to the current digital economic realities of students.